Actual Experience of Echocardiographic Evaluation of the Asymmetry of Atrioventricular Septal Defect in Patients with Different Anatomical Variants of Atrioventricular Septal Defect in the Choice of Optimal Surgical Approach - Shapoval, L. A.; Rudenko, N. M.; Dovgan, O. M.; Yemets, I. M. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Atrioventricular septal defect (AVSD) is a complex congenital heart defect caused by the abnormal structure of atrio-ventricular septum above and below the level of atrioventricular (AV) valves. Such a disturbance of the structure leads to the formation of a common opening of the AV valve which connects both atria with both ventricles. As a rule, AV junction is symmetrical, which results in an even and balanced flow of blood to each ventricle. However, there is a spectrum of non-uniform AV junction which is associated with hypoplasia of the left or right ventricle. In such cases, the AVSD is defined as unbalanced and characterized by varying degrees of AV junction displacement, hypoplasia of one of the ventricles and anomalies of the valve structures of the common AV valve. The main task in determining the imbalance of AV junction is to predict the left ventricle capacity to maintain systemic circulation, which is important in choosing the optimal surgical approach. The current trend is to combine new concepts and diagnostic criteria already described in order to determine the best way of treating children with such a complex congenital heart anomaly. The objective is to analyze the main echocardiographic indicators that determine the imbalance in patients with differ-ent anatomical variants of AVSD and to reveal correlation of these indicators with the dimensions which characterize the “ventricular geometry” in accordance with the chosen surgical approach. Material and methods. From January 2014 to December 2018, 279 patients with different anatomic variants of AVSD underwent examination and surgical treatment. Balanced AVSD was diagnosed in 245 (87.8%) patients (group I), the re-maining 34 (12.2%) patients had a certain degree of imbalance in the common AV valve (group II), of these 27 (9.8%) had unbalanced right-dominant AVSD, and 7 (2.5%) had unbalanced left-dominant AVSD. For the determination of anatomical features, the following echocardiographic parameters were used: modified atrio-ventricular valve index (mAVVI), right and left ventricular inflow angle (RV/LV inflow angle), left ventricular inflow index (LVII), end-diastolic area of LV and RV, end-systolic area of LV and RV, and linear dimensions of both ventricles and AV valves. Results. All patients in group I underwent biventricular repair. 188 (67.4%) patients had primary repair, 58 (20.4%) patients had total repair after diminution of the pulmonary artery. Patients of group ІІ diagnosed with right-dominant un-balanced AVSD had various degrees of LV hypoplasia. Four patients underwent modified Norwood operation as a stage I of single-ventricular repair. In 23 patients with right-dominant AVSD, total repair was performed. Of 7 patients with unbal-anced left-dominant AVSD, 3 (2.2%) had one and a half ventricular repair and 4 (1.4%) underwent biventricular repair of the anomaly. Comparing different echocardiographic imbalance indices, it was found that mAVVI moderately correlated with the di-ameter of the left AV valve annulus (r = 0.775, p < 0.0001) and with the end-diastolic area of the LV (r = 0.531, р < 0.0001), and slightly correlated with the diameter of the right AV valve annulus (r = 0.23, р = 0.0013) and with the end-diastolic area of the RV (r = 0.240, р = 0.001). The RV/LV inflow angle moderately correlated with the diameter of the left AV valve annu-lus and the diameter of the right AV valve annulus (r = 0.861, p < 0.0001and r = 0.775, p < 0.0001, respectively) and does not significantly correlate with the end-diastolic area of the LV and the end-diastolic area of the RV. The slight LVII correlation with LV end-diastolic area (r = 0.101, р = 0.880) and slight LVII correlation with the diameter of the left AV valve annulus were found. LVII had moderate correlation with the diameter of the right AV valve annulus (r = 0.175, р = 0.021). There is no LVII correlation with the end-diastolic area of the RV. Conclusion. Comparing different echocardiographic imbalance indices, it was found that mAVVI moderately correlated with the diameter of the left AV valve annulus imbalance indices have slight or moderate correlation with ventricular dimen-sions, indicating that none of these indicators should be used independently in determining the degree of balance and the choice of surgical approach in patients with different anatomical variants of AVSD.